Communicating Climate Smart Agriculture to the Stakeholders: Impact of LI-BIRD/CCAFS Travelling Seminars in Climate Smart Villages of Nepal : An Impact Assessment Report - Bhusal, Aastha; Khatri, Laxman; Neupane, Santosh; Yadav, Nagdev; Khatri-Chhetri, Arun; Malla, Yam (Local Initiatives for Biodiversity, Research and Development, Nepal, 2019)
This report presents the findings of an assessment of the impact of travelling seminar (TS) organized by Local Initiatives for Biodiversity, Research and Development (LI-BIRD)/Climate Change, Agriculture and Food Security (CCAFS) under the Climate Smart Village (CSV) project in Nepal. The travelling seminar impact assessment aimed at assessing the effectiveness of travelling seminar and to what extent the participants, especially the municipal and provincial level women leaders were able to internalize and apply the seminar learning to advocate and influence municipal and provincial level policies, plans and programmes for integrating climate smart agricultural technologies and practices. The assessment was carried out during 10-17 September 2019 at Bardibas (Mahottari district), Kawasoti (Nawalpur district) and Pokhara (Kaski district) with the involvement of mixed group of men and women representing the Federal House of Representatives, Province 2 Assembly and Gandaki provincial assembly, municipalities, and civil society organizations. Focus group discussion (FGD) and key informant interview (KII) were applied during the assessment. Results shows that the travelling seminar serves as an effective mechanism to share and learn about the technologies and practices through direct observation and to understand the real problems at community level through interaction with the users and beneficiaries. The travelling seminar is an important tool and method to influence local and provincial level policies, programmes and plans for scaling up of climate smart agricultural technologies and practices across Nepal.